Kerentanan Penghidupan Masyarakat Pesisir Perkotaan Terhadap Variabilitas Iklim (Studi Kasus di Kota Kupang) - Ledoh, Liky; Satria, Arif; Hidayat, Rahmat (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Adaptation to climate change cannot be separated from the climatic conditions and vulnerability of local communities. This study aims to determine the vulnerability of household livelihoods in urban coastal areas to climate variability. This research was conducted in coastal city of Kupang. Community livelihood vulnerability analysis using vulnerability index (LVI and LVI-IPCC). In addition, an analysis of climate variability of rainfall and average temperature from 1988-2017 was also carried out. The results of the study show that climate variability is seen in decreases in rainfall and and increase in surface temperature in the past 30 years. The LVI and LVI-IPCC scores also show the vulnerability of livelihoods on a medium scale in three sample villages. Climate variability in urban coasts can have an impact on coastal communities on the components of livelihood strategies, food, homes and land and water which are generally influenced by climatic factors. Non-vulnerable components such as health support the vulnerable components as part of the adaptation process